Valve timing study of a single cylinder motorcycle engine - Jefry, Dedi Efendi (2009)
In an internal combustion engine, valve timing is an important design parameter which affects many engine performance parameters. In this study, the effect of intake timing of an engine was investigated. The engine used in this study combines a 4-stroke engine bottom end with an opposed piston in the cylinder head working at half the cyclical rate of the bottom piston. Functionally, the second piston replaces the valve mechanism of the original engine that use poppet valve to control intake and exhaust port opening and closing. For the analysis, Computational Fluid Dynamic (CFD) software has been used to analyze in-cylinder air flow motion during intake stroke process with engine speed of 4000 rpm. The intake port of the engine was modified to vary the intake timing. The modification of intake port was done by using Computer Aided Design (CAD) software, Solidwork. From the CFD analysis, the in-cylinder air flow pattern and flow distribution before and after intake port modification was clarified. Simulation result shows that as the diameter of the port is decreased, the pressure drop and velocity of air flow into the engine cylinder are increased. Modification of the intake port shape from curved port to straight port was result in more symmetrical in-cylinder air flow distribution along the cylinder axis. For further study, it is strongly recommended to verify the simulation result with the experiment result as soon as the engine was successfully fabricated.